Pengaruh Dimensi-dimensi Kewargaan Korporat Persepsian pada Niat Melamar Pekerjaan dengan Ekspektasi Sukses Karir Sebagai Variabel Pemediasi - , DIKANAYA TARAHITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Business competition encourages companies to discover and strengthen their competitive advantages. Recruit and select high quality employees as companyâs human capital are important to allow the business to be sustained in the industry. The growing interest in Corporate Citizenship, widely known as Corporate Social Responsibility (CSR) in Indonesia, further affected companyâs policy and practice in recruitment process. Perceived corporate citizenship is proposed to have positive impact on job pursuit intention. Recent studies were treated corporate citizenship as a single dimension construct. Therefore, this study is aimed to test and analyze the impact of 4 perceived dimensions of corporate citizenship on job pursuit intention with career success expectation included as the mediating variable. The 4 dimensions tested in this study are perceived economic, legal, ethic, and philanthropic citizenship. The proposed hypotheses of this research are empirically tested using the data from 113 undergraduate students of Universitas Gadjah Mada. The empirical findings succeed to investigate and prove that perceived economics, legal, ethics, and philanthropic citizenship positively affect job pursuit intention and fostering optimistic career success expectation. Career success expectation is partially mediated the model. Among those 4 dimensions, philanthropic citizenship is found to give the highest contribution to the model. The purpose of these findings are to complement the growing literature in human resource management, especially in recruitment process and to bring a new perspective and approach for companyâs practice for considering the implementation of corporate citizenship to attract potential job seeker.